Solution:
The formula for tan(A+B) and tan(A-B) are:
![tan(A+B) = (tan(A)+tan(B))/(1-tan(A)tan(B)) \\\\tan(A-B) = (tan(A)-tan(B))/(1+tan(A)tan(B))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5uckzu0fm4wxo7erj7gm0jhs97ej8aa9g8.png)
The left hand side of the given expression is:
![tan((\pi)/(4)-\alpha ) tan((\pi)/(4)+\alpha )](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ds0uujr4m2yd8gf9xu7mbog6m1bugj2r75.png)
Using the formula above and value of tan(π/4) = 1, we can expand this expression as:
![tan((\pi)/(4)-\alpha ) tan((\pi)/(4)+\alpha )\\\\ = (tan((\pi)/(4) )-tan(\alpha))/(1+tan((\pi)/(4) )tan(\alpha)) * (tan((\pi)/(4) )+tan(\alpha))/(1-tan((\pi)/(4) )tan(\alpha))\\\\ = (1-tan(\alpha))/(1+tan(\alpha)) * (1+tan(\alpha))/(1-tan(\alpha))\\\\ = 1 \\\\ = R.H.S](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jilrd1u1gln9l4rdyacw9baerfzqukwmpe.png)
Thus, the left hand side is proved to be equal to right hand side.